Speak Up, Stand Out: Program untuk Mengembangkan Kemampuan BBerbicara yang Fasih dan Percaya Diri di UPT SMP Negeri 17 Makassar - Khairuddin H; Salsyabila, Andi Namirah Rezky; Fitriyani; Ariyani, Amra; Muhayyang, Maemunah (Jurusan Bahasa Inggris, 2024)
Speaking and Literacy Camp is an activity or program designed by the first batch of AjarMi students and continued by the third batch of AjarMi team in 2024. by the third batch of AjarMi Team in 2024. This program aims to improve students' speaking and reading comprehension and foster a sense of confidence in using English. The main objective is to improve participants' speaking, literacy and language skills, as well as expand vocabulary, encourage creativity, build social skills, and improve self-confidence in a creative and fun way. The approach used in this program approach is the communication approach, which teaches English through creative and fun activities such as creative and fun activities such as spelling bee and opposite game. The expected outcome expected after participating in this activity is the ability of students to acquire and demonstrate increased basic knowledge of English, especially in speaking ability and confidence in communicating. Communication.